Malarial Fever Diagnosed and Treated in a Low Risk Endemic Area - Regmi, Dharma Raj; Basnet, N.; Jaishwal, C.; Pun, S. (Journal of Karnali Academy of Health Sciences, 2018)
A case of a 2-year-old female child who initially presented with fever, later diagnosed and successfully treated as Malaria in Jajarkot Hospital in the District of Jajarkot which is a low malarial prevalence region. Patient had been treated with oral antibiotics in a local out of hospital pharmacy but continued to remain febrile. Patient admitted for evaluation of fever and inability to feed. Malaria was confirmed with ICT based Rapid Diagnostic Test after other foci/infection with high degree of suspicion were ruled out. Patient was treated based on the recent national guideline and eventually discharged after showing significant signs of improvement. This isolated case of malaria in a hilly low risk area like Jajarkot emphasizes the need to remain vigilant and adopt a stringent protocol-based diagnostic for diagnosis and treatment of a febrile patient.